Cholesterol metabolism as a prognostic marker in patients with mildly symptomatic nonischemic dilated cardiomyopathy. Issue 6 (June 2017) - Sawamura, Akinori; Okumura, Takahiro; Hiraiwa, Hiroaki; Aoki, Soichiro; Kondo, Toru; Ichii, Takeo; Furusawa, Kenji; Watanabe, Naoki; Kano, Naoaki; Fukaya, Kenji; Morimoto, Ryota; Bando, Yasuko K.; et al.
Abstract: Background: Little is known about whether the alteration of cholesterol metabolism reflects abdominal organ impairments due to heart failure. Therefore, we investigated the prognostic value of cholesterol metabolism by evaluating serum campesterol and lathosterol levels in patients with early-stage nonischemic dilated cardiomyopathy (NIDCM). Methods: We enrolled 64 patients with NIDCM (median age 57.5 years, 31% female) with New York Heart Association functional class I/II. Serum campesterol and lathosterol levels were measured in all patients. The patients were then divided into four subsets based on the median non-cholesterol sterol levels (campesterol 3.6 μg/mL, lathosterol 1.4 μg/mL): reference (R-subset), high-campesterol/high-lathosterol; absorption-reduced (A-subset), low-campesterol/high-lathosterol; synthesis-reduced (S-subset), high-campesterol/low-lathosterol; double-reduced (D-subset), low-campesterol/low-lathosterol. Endpoint was a composite of cardiac events, including cardiac-related death, hospitalization for worsening heart failure, and lethal arrhythmia. Results: Median brain natriuretic peptide (BNP) level was 114 pg/mL. Mean left ventricular ejection fraction was 31.4%. D-subset had the lowest total cholesterol level and cardiac index and the highest BNP level and pulmonary capillary wedge pressure. D-subset also had the highest cardiac event rate during the mean 3.8 years of follow-up (log-rank p  = 0.001). Multivariate regression analysis showed that D-subset was an independent determinant of cardiac events. The receiver operating characteristic curve analysis revealed that total cholesterol <153 mg/dL was a best cut-off value for discrimination of the D-subset. Conclusions: The combined reduction of campesterol and lathosterol that indicated intestinal cholesterol absorption and liver synthesis predicts future cardiac events in patients with mildly symptomatic NIDCM.